A mathematical perspective for the behavior of Covid-19 in Boyacá - Cruz, David Octavio (Uptc, 2021)
This article presents the initial results of a study whose purpose is to develop a behavioral forecast of the Covid-19 pandemic in the department of Boyacá using GeoGebra, OriginPro8, and Excel software. The data recorded by the Boyacá Health Secretary and by the National Institutes of Health in a period of 108 days since the first cases appeared, are classified according to the number of confirmed, infected, recovered, and deceased cases. A quantitative methodology with a documentary approach is used in order to create a deterministic strategy with a statistical balance. The result is an analysis and a projection of growth in the cases of Covid-19 based on exponential mathematical models, diagrams, and curves that represent the various phenomena that influence the statistical study and their variations according to the measures adopted by the Boyacá community.